Gas-Chromatographic Separation of Hydrogen Isotopes Mixtures on Capillary Molecular Sieve 5A Column - Preda, Anisoara; Bidica, Nicolae; Barbu, Cristina; Sbirna, Simona; Popescu, Alexandru; Pearsica, Claudia; Vasut, Felicia (Asian Journal of Chemistry, 2010)
Gas chromatography is a method for separating components of mixtures of volatile compounds. In most applications, the separations are made to identify and determine the quantity of each component of the sample of the mixture and analytical gas chromatographic apparatus includes additional devices for this purpose. The method for separating the isotopic species of hydrogen on a moderately large scale using low temperature gas chromatography. In this paper, this method is proposed for the analysis of gas mixtures containig hydrogen isotopes. The species isotopic of hydrogen are: H2, D2, T2, HD, HT, DT, where D stands for 2H and T for 3H. The method is based on the substantial difference in the thermal conductivity of these isotopes.